Interfragmentary Fixation in Unilateral Zygomaticomaxillary Complex Fractures: Serial Cases - Ivanny, Putri Sari; Hafiz, Al (PERHATI-KL, 2022)
ABSTRACTBackground: Zygomaticomaxillary complex (ZMC) is an integral part of the facial skeleton inanterolateral prominence thus makes it prone to injury. Common etiologies include motor vehicleaccidents, industrial accidents, sport injuries and interpersonal violence. Interfragmentary fixationtechnique is one of the surgery procedures for ZMC fracture. Purpose: To perform interfragmentaryfixation through subtarsal and extended subciliary incision on young and aged patients. Case Report:Reported cases of unilateral zygomaticomaxillary fracture in 75 years old male and 37 years oldfemale. Clinical Question: Does interfragmentary fixation using mini plates and screws provide goodresults on face reconstruction of ZMC fractures? Method: Literature searching was performed throughCochrane database, PubMed, Clinical Key and Google Scholar. Result: The search obtained 65literatures which were published in the last 10 years, and found 26 articles relevant with the topic.Conclusion: Interfragmentary fixation technique is one of surgery procedures for ZMC fractures thatgives satisfactory results in terms of function and aesthetics. ABSTRAKLatar belakang: Kompleks zigomatico maksilaris (KZM) merupakan bagian integral tulangwajah pada anterolateral, menonjol dan cembung sehingga rentan terhadap cedera. Sebagian besarfraktur KZM terjadi akibat kecelakaan lalu lintas, kecelakaan kerja, kecelakaan saat berolahraga dankekerasan interpersonal. Teknik fiksasi inter fragmen merupakan salah satu pilihan tindakan operatifpada fraktur KZM. Tujuan: Melakukan teknik fiksasi inter fragmen dengan pendekatan insisisubtarsal dan insisi sub siliar berlanjut pada pasien muda dan usia lanjut. Laporan Kasus:Dilaporkan dua kasus fraktur KZM unilateral pada pasien laki-laki usia 75 tahun dan perempuanusia 37 tahun. Pertanyaan klinis: Apakah fiksasi inter fragmen menggunakan plat dan sekrup (plateand screw) memberikan hasil yang baik pada rekonstruksi wajah fraktur KZM? Metode: Penelusuranliteratur dilakukan melalui Cochrane database, PubMed, Clinicalkey dan Google Scholar. Hasil:Ditemukan 65 literatur yang diterbitkan dalam 10 tahun terakhir, dan didapatkan 26 artikel yangrelevan dengan topik yang dibahas. Kesimpulan: Teknik fiksasi inter fragmen merupakan salah satupilihan tindakan operatif pada fraktur KZM.